2003
DOI: 10.1124/jpet.103.056291
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Residues in the Amino Terminal Domain of the Human NR2B Subunit Involved in the RO 25-6981 Binding Pocket

Abstract: N-Methyl-D-aspartate (NMDA) receptors play key roles in both physiological processes, particularly synaptic plasticity, and in neuropathological states such as epilepsy and acute neurodegeneration. R- (R‫,ء‬S‫-4(-␣-)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 31 publications
3
46
0
1
Order By: Relevance
“…This study and previous work (Perin-Dureau et al, 2002;Malherbe et al, 2003) show that the NR2B NTD is capable of binding two ligands of very distinct chemical nature, the Zn ion and bis-(phenylalkyl)amines such as ifenprodil. Kinetic analysis indicates that Zn and ifenprodil interact in a competitive manner (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study and previous work (Perin-Dureau et al, 2002;Malherbe et al, 2003) show that the NR2B NTD is capable of binding two ligands of very distinct chemical nature, the Zn ion and bis-(phenylalkyl)amines such as ifenprodil. Kinetic analysis indicates that Zn and ifenprodil interact in a competitive manner (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…In both NMDA and AMPA/kainate receptors, the NTD is a major, but not the sole, determinant of subtype-specific subunit assembly (Leuschner and Hoch, 1999;Ayalon and Stern-Bach, 2001;Meddows et al, 2001). Recent studies have also shown that, in certain NMDA receptor subunits, the NTD modulates ion channel gating through binding of extracellular allosteric modulators: Zn in the case of the NR2A subunit (Choi and Lipton, 1999;Fayyazuddin et al, 2000;Low et al, 2000;Paoletti et al, 2000) and the noncompetitive synthetic antagonist ifenprodil and its derivatives in the case of NR2B (Perin-Dureau et al, 2002;Malherbe et al, 2003). Because Zn is known to be concentrated and released during activity at many glutamatergic synapses in the CNS (Frederickson et al, 2000), it appears to be a likely candidate as the endogenous ligand of the NTD of NR2A.…”
Section: Introductionmentioning
confidence: 99%
“…Ifenprodil was identified as a GluN1/GluN2B selective inhibitor (Williams, 1993) and originally was thought to solely bind to the GluN2B ATD (Perin-Dureau et al, 2002;Malherbe et al, 2003;Wong et al, 2005;Ng et al, 2008). Ifenprodil preferentially binds the receptor in open and desensitized conformations (Kew et al, 1996) and reduces the duration of the long openings and open probability of the receptor in cultured hippocampal neurons (Legendre and Westbrook, 1991) and in hippocampal slices from newborn rats (Pina-Crespo and Gibb, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, with few exceptions, there remains a lack of comprehensive glutamate receptor subunit-selectivity data for most ligands. Although the structural diversity of active ligands suggests that the binding site can accommodate different molecular scaffolds in different binding poses, few data exist with which to evaluate the idea that the compounds may share some overlapping, but not all, atomic contacts within GluN2B (Malherbe et al, 2003;Marinelli et al, 2007;Mony et al, 2009b).…”
Section: The Glun2b Amino-terminal Domain Harbors a Binding Site For mentioning
confidence: 99%